Enhanced dynamic hand gesture recognition for finger disabilities using deep learning and an optimized Otsu threshold method - Kadhim, Malik Kareem; Der, Chen Soong; Chai Phing, Chen (Engineering Research Express, 2025)
Hand gestures serve as a powerful means of communication, capable of conveying extensive information across various public health domains, including medicine and education. The process of hand gesture recognition involves the use of mathematical algorithms to identify human gestures and finds applications in areas such as communication for the deaf, human-computer interaction, intelligent driving, and virtual reality. This study introduces a robust method aimed at recognizing dynamic hand gestures, particularly for individuals with finger disabilities. The approach begins with segmenting hand gestures from intricate backgrounds using an advanced Otsu segmentation algorithm, while also integrating motion data from RGB video sequences. Hand gestures are transformed into texture and contour features, which are utilized as input for a hybrid model that merges a convolutional neural network (CNN) with a recurrent neural network (RNN). The model employs Inception-v3 for feature extraction complemented by an LSTM layer for classification. The focus of the study is on recognizing six dynamic gestures, with particular emphasis on ‘scroll right’ and ‘scroll down’ due to their high accuracy in recognition. The model demonstrated an average precision of 84.34% across all gestures, achieving 87.57% for gestures involving finger impairments. These results highlight the model’s effectiveness in practical applications for dynamic hand gesture recognition.